The Effect of Different Doses of Boster Grotop in the Feed on the Growth and Survival Rate of Asian Redtail Catfish (Hemibagrus nemurus) Maintained in Peat Swamp Media - Jr, Muchlisul Amal; Pamukas, Niken Ayu; Mulyadi, Mulyadi (Fakultas Perikanan dan Kelautan Universitas Riau, 2021)
This study aims to determine the effect of different doses of booster grotop in feed on the growth and survival of Asian Redtail (Hemibagrus nemurus) maintained in peat swamp media. This research was conducted from 27 March - 05 May 2020 at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The container used was an aquarium measuring 60 cm x 40 cm x 40 cm as many as 15 units with a stocking density of 12 fish/60 L. This study used a completely randomized design method (CRD) one factor with five levels of treatment and three repetitions. The level of treatment applied in the study was P0 = without giving Boster Grotop (Control), P1 = dose of Boster Grotop 25 g/kg of feed, P2 = dose of Boster Grotop 30 g/kg of feed. P3 = dose of Boster Grotop 35 g/kg of feed and P4 = dose of Boster Grotop 40 g/kg of feed. The results showed that giving boster grotop with different doses in the feed had a significant effect (P<0.05) on growth but had no significant effect (P>0.05) on the survival rate of the Asian Redtail seeds. The best treatment was found at a boster grotop dose of 40 g/kg of feed, which produced protease enzyme activity (0.1731 IU/mL), total weight growth (5.11 g), total length growth (3.73 cm), specific growth rate (3.67%), feed efficiency (72.30%), feed conversion (1.38), survival rate (86.11%).